Seasonal changes in the concentration and metabolic activity of bacteria and viruses at an Antarctic coastal site - Bell, Elanor M. (2007)
Bacteria play a key role in the world's oceans, supporting nutrient remineralisation and mediating carbon transfer. Little is known about annual changes in bacterial concentration, production and metabolism during the extreme seasonal changes in biological productivity in Antarctic waters. We measured rates of bacterial production, concentrations of viruses and bacteria and environmental parameters between February 2004 and January 2005 at an Antarctic coastal site. Concentrations of total bacteria and viruses were obtained using 4', 6-diamidino-2- phenylindole (DAPI) and SYBR Green I (Molecular Probes), respectively. Populations of bacteria in different metabolic states were estimated using vital stains. Concentrations of bacteria with intact or compromised plasma membranes were estimated using BacLight (Molecular Probes) and active cells estimated using 6-carboxyfluorescein diacetate (6CFDA). Our study showed 6CFDA and BacLight gave rapid and ecologically valuable insights into bacterial physiology, production and growth in natural Antarctic communities that were poorly represented by changes in total cell concentrations. Concentrations of total, active and intact bacteria declined rapidly at the end of summer probably owing to viral infection and microheterotrophic grazing. The decline continued over winter, likely owing to substrate limitation, and concentrations only increased after the phytoplankton bloom in spring and summer. Bacterial abundance was positively correlated with particulate organic carbon (POC) and nitrogen (PON), but not dissolved organic carbon (DOC), reflecting the refractory nature of the DOC pool. Only active and intact bacteria were significantly correlated with concentrations of chl a and rates of bacterial production. Furthermore, the obtained rates of [H-3]thymidine uptake suggest that bacterial growth rates can be sustained by the populations identified as intact or by active cells alone.